COMPARISON OF AXIAL LENGTH MEASUREMENT WITH CONTACT ANDNON-CONTACT BIOMETRY (The Research of Medical Science Review, 2024)
Background: Accurate axial length measurement is crucial for optimal intraocular lens (IOL) power calculation in cataract surgery. Both contact and non-contact methods are used, but their impact on post-operative outcomes remains unclear. Objective: To compare the effectiveness of contact versus non-contact axial length measurement methods on postoperative mean spherical equivalent in cataract patients. Methods: This randomized control trial was conducted over six months at the Cataract Clinic, Al Ibrahim Eye Hospital, Karachi. A total of 100 cataract patients were randomly assigned to Group A (non-contact IOL Master) or Group B (contact A-Scan) for axial length measurement. Post-operative mean spherical equivalent was assessed four weeks after surgery. Data were analyzed using SPSS, with t-tests and stratified analysis based on age and gender. Results: The non-contact method (Group A) showed a slightly better post-operative mean spherical equivalent (0.95 ± 0.12 D) than the contact method (1.00 ± 0.20 D), with a statistically significant difference (p = 0.04). Visual acuity improvements were similar in both groups, with 80% in Group A and 76% in Group B achieving 6/12 or better. Conclusion: The non-contact method provided slightly more accurate refractive outcomes and increased patient comfort, making it a preferable choice for axial length measurement in cataract surgery. Both methods, however, were effective in achieving satisfactory post-operative visual acuity.